2007
DOI: 10.1007/s12035-007-0024-z
|View full text |Cite
|
Sign up to set email alerts
|

TWEAK and the Central Nervous System

Abstract: Tumor necrosis factor-like weak inducer of apoptosis (TWEAK) is a member of the tumor necrosis factor superfamily that acts on responsive cells via binding to a cell surface receptor named fibroblast growth factor-inducible 14 (Fn14). TWEAK can regulate numerous cellular responses in vitro and in vivo. Recent studies have indicated that TWEAK and Fn14 are expressed in the central nervous system (CNS), and that in response to a variety of stimuli, including cerebral ischemia, there is an increase in TWEAK and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 96 publications
0
30
1
Order By: Relevance
“…Members of this superfamily have roles in many biological events including immune system development and function (Wiley and Winkles, 2003) as well as in the pathogenesis of many central nervous system diseases such as multiple sclerosis and cerebral ischemia (Feuerstein et al, 1997;Juedes et al, 2000). A relatively recently found member of this family, TNF-related weak inducer of apoptosis (TWEAK), and its receptor fibroblast growth factor-inducible 14 (Fn14) are shown to have importance both in development of pathological processess and as a target for the treatment of these diseases (Yepes, 2007).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of this superfamily have roles in many biological events including immune system development and function (Wiley and Winkles, 2003) as well as in the pathogenesis of many central nervous system diseases such as multiple sclerosis and cerebral ischemia (Feuerstein et al, 1997;Juedes et al, 2000). A relatively recently found member of this family, TNF-related weak inducer of apoptosis (TWEAK), and its receptor fibroblast growth factor-inducible 14 (Fn14) are shown to have importance both in development of pathological processess and as a target for the treatment of these diseases (Yepes, 2007).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Its expression has been detected in brain, heart, skeletal and smooth muscle, pancreas, spleen and lymphocytes (Yepes, 2007). In addition, expression of its receptor Fn14 is found to be high on most tumor cell lines of non-lymphoid origin and low on fibroblasts and endothelial and epithelial cells of healthy tissue (Burkly et al, 2011;Wajant, 2013).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…TWEAK expression is more prominent in astrocytes, and Fn14 expression is found predominantly in neurons [reviewed in Ref. (35)]. Early studies using murine models of focal cerebral ischemia showed that both TWEAK and Fn14 mRNA expression in ischemic brain tissue increases within hours after an ischemic insult (3638).…”
Section: Tweak/fn14 Axis-targeted Therapeutics: Inflammatory And/or Nmentioning
confidence: 99%
“…Fn14 is normally expressed at relatively low levels in healthy tissue. In the brain, Fn14 is found in endothelial cells, astrocytes, neurons, and microglia at baseline, with a further increase in expression following exposure to various inflammatory stimuli [16]. Among the main effects induced by TWEAK and Fn14 interactions are inflammation, and cell death or cell proliferation depending on the particular cell type and cytokine context [17].…”
Section: Introductionmentioning
confidence: 99%